Resposta :
A reta [tex]g(x)[/tex] tangente à função [tex]f(x)[/tex] no ponto [tex]x=x_0[/tex] é dada por:
[tex]f'(x_0)=\frac{g(x)-f(x_0)}{x-x_0}[/tex]
[tex]g(x)-f(x_0)=f'(x_0)(x-x_0)[/tex]
[tex]g(x)=f(x_0)+f'(x_0)(x-x_0)[/tex]
Onde [tex]f'(x_0)[/tex] é igual à derivada de [tex]f(x)[/tex] no ponto [tex]x=x_0[/tex].
a)
Derivando [tex]f(x)[/tex], achamos que [tex]f'(x)=2x-5[/tex] logo [tex]f'(2)=2\cdot2-5=-1[/tex]. Temos então que:
[tex]g(x)=f(2)+f'(2)(x-2)[/tex]
[tex]g(x)=2^2-5\cdot2+6-(x-2)[/tex]
[tex]g(x)=-x+2[/tex]
b)
Derivando [tex]f(x)[/tex]:
[tex]f'(x)=\frac{\frac{d}{dx}(x-1)\cdot(x+3)-\frac{d}{dx}(x+3)\cdot(x-1)}{(x+3)^2}[/tex]
[tex]f'(x)=\frac{1\cdot(x+3)-1\cdot(x-1)}{(x+3)^2}[/tex]
[tex]f'(x)=\frac{x+3-(x-1)}{(x+3)^2}[/tex]
[tex]f'(x)=\frac{4}{(x+3)^2}[/tex]
logo [tex]f'(3)=4/[(3+3)^2]=4/36=1/9[/tex]. Temos então que:
[tex]g(x)=f(3)+f'(3)(x-3)[/tex]
[tex]g(x)=\frac{3-1}{3+3}+\frac{1}{9}\,(x-3)[/tex]
[tex]g(x)=\frac{1}{3}+\frac{x}{9}-\frac{1}{3}[/tex]
[tex]g(x)=\frac{x}{9}[/tex]
c)
Derivando [tex]f(x)[/tex], achamos que [tex]f'(x)=\cos x[/tex] logo [tex]f'(\pi/4)=\cos\pi/4=\sqrt{2}/2[/tex]. Temos então que: